Impact of Road Humps on the Pavement Surface Condition - Mohamed Hamed Zakaria; Amal H. Al-Ayaat; Sayed A. Shwaly (Civil Engineering Journal, 2019)
In order to fight against over-speeding, the government and people in Egypt resorted to the installation of speed humps without adequate studies. On this basis, speed humps became widespread in most of the Egyptian roads in a semi-random way. It has been observed that the pavement condition of the roads has deteriorated in the vicinity of these humps. For impact assessment of speed humps on the pavement condition index (PCI), three roads link Kafr El-Sheikh city with three major towns in Kafr El-Sheikh governorate were selected to conduct PCI survey. The results indicated that the presence of speed humps contributes greatly to reduce the pavement condition index (PCI) values. It should be mentioned that the average reduction in PCI values ranged between 15% and 22% due to the presence of speed humps. Also, the most frequently observed distress on the pavement sections including humps considered for the selected roads was Raveling and Rutting. Accordingly, to avoid the pavement defects at the locations where the speed humps are installed, it is proposed to study the structural section of the road in the vicinity of the speed hump to resist the braking force and speed reduction effect.